2019
DOI: 10.3390/molecules24091673
|View full text |Cite
|
Sign up to set email alerts
|

Mulinum crassifolium Phil; Two New Mulinanes, Gastroprotective Activity and Metabolomic Analysis by UHPLC-Orbitrap Mass Spectrometry

Abstract: Mulinum crassifolium Phil. (Apiaceae) is an endemic shrub from Chile commonly used as infusion in traditional medicine to treat diabetes, bronchial and intestinal disorders and stomach ailments, including ulcers. From the EtOAc extract of this plant, the new mulinane-type diterpenoids 3 and 5 were isolated along with three known diterpenoids. The gastroprotective effect of the infusion of the plant was assayed to support the traditional use and a fast HPLC analysis using high resolution techniques was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Upon fragmentation by collision–induced dissociation (CID), these compounds produced the ions at m/z 289, 287, 271, 253, 229, 135, 113, 95, 87, 83, 69, 57. In particular, Areche et al, in 2019, reported the ion fragment at m/z 135 for 14 α -hydroxymulin-12-en-11-one-20-oic acid, a mulinane diterpenoid [ 30 ]. The signal at 16.61 min in IV sub-fraction ( 5 ) with m/z 497.27 indicated the presence of an extra hexose sugar unit with respect to m/z 333.20 and it was putatively identified as mulinic acid hexoside derivative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon fragmentation by collision–induced dissociation (CID), these compounds produced the ions at m/z 289, 287, 271, 253, 229, 135, 113, 95, 87, 83, 69, 57. In particular, Areche et al, in 2019, reported the ion fragment at m/z 135 for 14 α -hydroxymulin-12-en-11-one-20-oic acid, a mulinane diterpenoid [ 30 ]. The signal at 16.61 min in IV sub-fraction ( 5 ) with m/z 497.27 indicated the presence of an extra hexose sugar unit with respect to m/z 333.20 and it was putatively identified as mulinic acid hexoside derivative.…”
Section: Resultsmentioning
confidence: 99%
“…and other species belonging to the Apiaceae family [ 64 ]. Many studies have been reported the different biological activities of these terpenoid compounds, including their antibacterial [ 31 ], antituberculosis [ 65 ], gastroprotective [ 30 ] and antitumor activity [ 34 , 36 ]. In particular, many of the putatively compounds present in AG have important cytotoxic activity; for examples, Bórquez et al showed cytotoxic effect of azorellanes on human breast carcinoma cells; their activity was dependent on their beta acetate group at position C -7 in the skeleton [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of different functional groups, which include hydroxyl, carboxyl, acetoxy, and double bond, in the mulinane skeleton has allowed the preparation of a significant number of semisynthetic derivatives using dehydration, alkylation, hydrolysis, and oxidation reactions ( Table 3, and Figure 5). To date, only one semisynthetic azorellane derivative, 7β-deacetylazorellanol (16), has been reported; this can be explained by the fact that the cyclopropane ring in the azorellane skeleton can be easily open under weak acidic conditions, to produce semisynthetic derivatives having a mulinane skeleton [54]. However, the limited number of functionalized positions, and the type of functional groups, found in the chemical structures of natural azorellane and mulinane diterpenoids limit the number and type of semisynthetic derivatives that can be prepared through chemical modification [55]; because of this, in recent years, biotransformation using filamentous fungi such as Mucor plumbeus and M. circinelloides has been explored as a new strategy to obtain novel mulinane and azorellane derivatives [51,55,56] (Table 4, Figure 6).…”
Section: Synthetic Semisynthetic and Biotransformed Mulinane And Azmentioning
confidence: 99%
“…A search for bioactive metabolites with anti-inflammatory and analgesic properties produced by A. compacta, A. yareta, and L. acaulis resulted in the identification of azorellanol (9), azorellanone (17), and 7β-deacetylazorellanol (16); azorellanol (9) showed anti-inflammatory activity when tested on arachidonic acid (AA) and 12-deoxyphorbol-13-Tetradecanoate (TPA)-induced edemas. The fact that (9) showed a higher activity on the TPA than in the AA-induced edema assays (dose: 15 × 10-7 mol/ear) and that the dermal anti-inflammatory activity was of 70.8%, suggests that the mechanism of action of (9) could involve the inhibition of cyclo-oxygenase activity.…”
Section: Anti-inflammatorymentioning
confidence: 99%
See 1 more Smart Citation